EXPLORING EMPLOYEE PERCEPTIONS OF FAIRNESS IN PERFORMANCE APPRAISAL SYSTEMS: A STUDY OF ANUDU PLASTIC FACTORY ASABA, DELTA STATE. (UNIZIK Journal of Marketing, 2025)
This study explored employee perceptions of fairness in performance appraisal systems at Anudu Plastic Factory. Performance appraisal is a crucial human resource management practice, yet employee dissatisfaction often stems from perceived unfairness in its implementation. The research adopted a qualitative approach, using in-depth interviews to gather insights from selected employees across different departments. The study focused on three dimensions of fairness: distributive fairness, procedural fairness, and interactional fairness. Findings revealed that while some employees acknowledge the appraisal system as moderately fair, many express concerns about bias, lack of transparency, and inadequate communication during the appraisal process. These perceptions significantly affect employee morale, motivation, and trust in management. The study recommends that Anudu Plastic Factory review its appraisal criteria, improve communication, and provide regular feedback to ensure fairness and employee acceptance of performance evaluations.
Keywords: Employee Perceptions, Performance Appraisal, Fairness, Distributive Fairness, Employee Motivation, Organizational Trust.